Implementing the ITPGRFA in Bhutan, Burkina Faso, Costa Rica, Côte d’Ivoire, Guatemala, Nepal, Rwanda and Uganda: highlights - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
With technical support of Bioversity International, government organizations in eight countries developed policies/laws, introduced these into national policy processes to create policy/legal space for Treaty implementation, identified genetic resources within their country to be included in the multilateral system, designated national competent authorities capable to consider requests for access to plant genetic resources for food and agriculture and sharing of those resources with users worldwide. The eight countries are implementing the Treaty and Nagoya Protocol in a mutually supportive way.